2019
DOI: 10.1021/acs.jpcc.9b05419
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photoelectrochemical Oxidation of Water over Ti-Doped α-Fe2O3 Electrodes by Surface Electrodeposition InOOH

Abstract: Ti-doped α-Fe 2 O 3 (Ti-Fe 2 O 3 ) is regarded as one of the most promising hematite-based photoanodes for photoelectrochemical oxidation of water. However, the sluggish interfacial transfer and rapid recombination of photogenerated holes still limit its efficiency. In this article, we report that an approach of surface modification for this material by electrodeposition in In(NO 3 ) 3 containing aqueous solutions was attempted to overcome these disadvantages. The results show that a thin layer of InOOH was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 42 publications
2
25
0
Order By: Relevance
“…In addition, as illustrated in Figure , for less positive applied potentials, optical signals can be observed in three of our studied photoanodes, indicative of charge accumulation in intra-bandgap states. Charge accumulation in such intra-bandgap states has previously been reported for hematite in several studies and proposed to drive water oxidation. In contrast, the data herein shows that charge accumulating in these states does not contribute significantly to water oxidation, most likely due to their modest oxidation potentials relative to hematite’s valence band. These intra-bandgap states have been suggested to be catalytically inactive, instead, they are likely involved in competing trapping processes that can be mitigated with increasing applied potentials.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…In addition, as illustrated in Figure , for less positive applied potentials, optical signals can be observed in three of our studied photoanodes, indicative of charge accumulation in intra-bandgap states. Charge accumulation in such intra-bandgap states has previously been reported for hematite in several studies and proposed to drive water oxidation. In contrast, the data herein shows that charge accumulating in these states does not contribute significantly to water oxidation, most likely due to their modest oxidation potentials relative to hematite’s valence band. These intra-bandgap states have been suggested to be catalytically inactive, instead, they are likely involved in competing trapping processes that can be mitigated with increasing applied potentials.…”
mentioning
confidence: 79%
“…One of the key considerations for water oxidation on metal oxides, including hematite, is the potential role of intra-bandgap surface states. Such surface states have often been related to oxygen vacancies and structural imperfections/defect sites. Surface holes on hematite have been assigned to Fe IV O species, with these states being proposed as the first intermediate species of the OER . Some studies, including electrochemical impedance analyses, have provided evidence that midgap surface states participate as intermediates in the OER catalysis on such photoanodes. Other studies, including transient absorption analyses, have suggested OER catalysis is driven by valence band holes localized at the metal oxide surface, with intra-bandgap (e.g., oxygen vacancy) states primarily functioning as electron/hole trapping sites, impacting upon bulk and back electron–hole recombination. , The impact of surface states on the water oxidation catalysis on metal-oxide photoanodes such as α-Fe 2 O 3 therefore remains controversial.…”
mentioning
confidence: 99%
“…Charge accumulation in such intra-bandgap states has previously been reported for hematite in several studies, and proposed to drive water oxidation. [13][14][15][16] In contrast, the data herein shows that charge accumulating in these states does not contribute significantly to water oxidation, most likely due to their modest oxidation potentials relative to hematite's valence band. These intra-bandgap states have been suggested to be catalytically inactive, 38 instead, they are likely involved in competing trapping processes that can be mitigated with increasing applied potentials.…”
Section: Rhementioning
confidence: 97%
“…12 Some studies, including electrochemical impedance analyses, have provided evidence that mid-gap surface states participate as intermediates in the OER catalysis on such photoanodes. [13][14][15][16] Other studies, including transient absorption analyses, have suggested OER catalysis is driven by valence band holes localized at the metal oxide surface, with intra-bandgap (e.g. : oxygen vacancy) states primarily function as electron / hole trapping sites, impacting upon bulk and back electron-hole recombination.…”
mentioning
confidence: 99%
“…[8][9][10] Considering the above, the targeted modification of α-Fe 2 O 3 is necessary to increase its PEC activity by: (i) nanoengineering α-Fe 2 O 3 to compensate for the short minority carrier diffusion length by maximizing the semiconductor-electrolyte interface; 11,12 (ii) increasing the electroconductivity by elemental doping (e.g., F, Ti, Ta); 7,13,14 (iii) passivating the surface states by the decoration of a metal oxide transition layer; 15,16 (iv) heterostructure engineering by utilizing the synergistic effects of different semiconductors; 17,18 and (v) loading cocatalyst to improve the water oxidation kinetics. 19 The state-of-the-art cocatalysts mainly include transition metal oxides (CoO X ), 20 hydroxides (Ni(OH) 2 ), 21 oxyhydroxides (FeOOH, NiOOH, InOOH), [21][22][23] and phosphates (CoPi, FeP). 24,25 Metal borides exhibit extremely rich diversity in crystal structure and chemical bond formation; thus they have potential applications in the aspects of superconductivity, electronics, and catalysis.…”
Section: Introductionmentioning
confidence: 99%